2015
DOI: 10.1080/09645292.2015.1015405
|View full text |Cite
|
Sign up to set email alerts
|

Class size, school size and the size of the school network

Abstract: In many transition countries, including Ukraine, decreases in population and fertility have led to substantial falls in the number of school-aged children. As a consequence, these countries now have school networks that consist of many small schools, leading many countries to consider reorganizing their school networks by closing smaller schools and reallocating students. Using a rich dataset of almost the entire population of Ukrainian secondary schools, we estimate the effect of school size and class size on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Both these factors are highly significant regardless of whether a school sample covers the full dataset (652 schools; except vocational, evening and extramural schools) or excludes gymnasiums and middle schools (see Table ). The positive link between school size and pupil performance (see also Figure ) is in line with the literature (Burney et al., ; Coupe et al.,; Essid et al., ; Huguenin, ; Pereira & Moreira, ).…”
Section: Multifactor Analysissupporting
confidence: 90%
See 3 more Smart Citations
“…Both these factors are highly significant regardless of whether a school sample covers the full dataset (652 schools; except vocational, evening and extramural schools) or excludes gymnasiums and middle schools (see Table ). The positive link between school size and pupil performance (see also Figure ) is in line with the literature (Burney et al., ; Coupe et al.,; Essid et al., ; Huguenin, ; Pereira & Moreira, ).…”
Section: Multifactor Analysissupporting
confidence: 90%
“…Fourth, we follow Coupe et al. () when trying to control for the likely impact of socio‐economic factors on pupil performance by including the registered unemployment rate in the municipality (per cent; in February 2015 ) and the average net wage in the municipality (euro; 2014) . These data were extracted from the databases of the State Employment Agency and CSB, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tom and Alonso (2015) propose that class size does not have a considerable impact on students' outcome; if they do, it will be in neglectable numbers. However, they also found that there are significant correlations between the number of students at schools and the number of teachers at schools.…”
Section: Foreign Language Learning In Large Classesmentioning
confidence: 99%